The Closed Loop Controller for Mini Demo Biomass Power Plant Fuel-Feeding Arm based Pneumatic System - Poom Konghuayrob (My University, 2021)
This paper shows the establishment of a mini demo Biomass power plant fuel-feeding arm with controller, motor and pneumatics system to study how to control arm for picking and placing of fuel operation properly. The arm mechanical elements, control driver circuit and electrical components were designed, built and selected follows the real Biomass power plant fuel-feeding arm. Low level PID controller, proportional pneumatics valve and motor with encoder are utilized for defining the correct close loop position of mini demo arm. Moreover, this system is designed to plug with the Robot operating system (ROS) the easy robotics motion control system which use to calculate the desired position before sending to the robot arm close loop system. The results show the effectiveness of the established mini demo Biomass arm can archive the correct position even controlled by nonlinear air flow system.
Keywords: Image and Object Detection Techniques; Mineral Processing and Grinding; Industrial Automation and Control Systems